Challenges of Tsunami Risk Reduction on the Serang West Coast - Akhirianto, Novian Andri; Tiwi, Dwi Abad; Astisiasari, Astisiasari; Putra, Ahmad Pratama; Umbara, Raditya Panji; Shomim, Achmad Fakhrus; Ganesha, Deliyanti; Utari, Enggar (Indonesian Journal of Geography, 2025)
The 2018 Sunda Strait tsunami that was not sourced from tectonics earthquakes hit the west coast of Serang Regency as one of the affected areas. On this account, addressing the tsunami risk in this region shall be done wisely through the Disaster Risk Reduction (DRR) effort. This research aims to firstly examine the DRR that has been implemented after the 2018 tsunami, and secondly identify the internal and external environmental factors, as valuable input in developing the strategies on enhancing the tsunami resilience. This research has a qualitative descriptive study, using primary and secondary data sources. The data collection techniques employ the literature studies, interviews, FGDs, and field observations. Furthermore, this study applies SWOT analysis to identify the internal and external environmental factors. The results indicate the progresses made in tsunami DRR on the west coast of Serang Regency. However, although policies for coastal area planning and management have been established, there is still a need for community socialization, proper implementation, and enforcement of the law. Moreover, both of robust tsunami early warning system and public education on vandalism prevention is also needed. Finally, the results of identifying the internal and external environmental factors show that there are 3 strengths, 3 weaknesses, 3 opportunities and 3 challenges. Accordingly, the results of this identification can be used to formulate advance strategies in increasing the tsunami resilience on the west coast of Serang Regency. Received: 2024-03-20 Revised: 2024-05-03 Accepted: 2025-12-03 Published: 2025-12-04